A new linelist for the A3Π–X3Σ− transition of the NH free radical. (September 2018) - Fernando, Anton M.; Bernath, Peter F.; Hodges, James N.; Masseron, Thomas
Highlights: Calculated linelist for the NH A 3 Π-X 3 Σ- transition for v ′ = 0 − 2 and v ″ = 0 − 6 . New ab initio A-X transition dipole moment. Validation with astronomical spectra. Abstract: A new linelist for the A 3 Π– X 3 Σ − electronic transition of NH has been prepared using line positions from the literature and calculated line intensities. High level ab initio calculations were performed with the MOLPRO program to obtain the A – X transition dipole moment function. Potential energy curves and line strengths were calculated with Le Roy's RKR1 and LEVEL programs. Line intensities and Einstein A values were calculated with Western's PGOPHER program after converting the Hund's case (b) output of LEVEL to Hund's case (a) input needed for PGOPHER . The Herman–Wallis effect is included in the Einstein A calculations of the bands for the levels with v ′ = 0 − 2 and v ″ = 0 − 6 .